FORMULASI MASKER LUMPUR PERASAN BUAH PEPAYA (Carica papaya L.) DENGAN VARIASI KAOLIN - Erwan Kurnianto; Fadli Fadli; Ade Ferdinan; Andi Azis (Akademi Farmasi Yarsi Pontianak, 2021)
Papaya Fruit (Carica papaya L.) contains nutritious properties such as sucros, which can bu used as a moisturizer so that it can be used as a mud mask. Mud masks are one type of mask that is in demand. The main factor in the formation of sludge is clay minerals, for example, kaolin. Clay is clay formed from weathering aid granite that can harden and form a mass of solids along with the loss of water due to evaporation. This study aims to look at the effect of using kaolin base as a mud base on the physical properties of mud mask preparations. In this study, papaya ingredient of 10% each in each formula. Kaolin used as a base has a variety of concentration in each formula that is 40% (FI), 50% (FII) and 55% (FIII). The preparation of each formula was tested including organoleptic test, pH test and dispersion test. The test results show that all formulas meet the physical properties requierements including organoleptic test, pH test and dispersion test.